A Randomized Controlled Trial of Employer Matching of Employees' Monetary Contributions to Deposit Contracts to Promote Weight Loss. Issue 6 (July 2016) - Kullgren, Jeffrey T.; Troxel, Andrea B.; Loewenstein, George; Norton, Laurie A.; Gatto, Dana; Tao, Yuanyuan; Zhu, Jingsan; Schofield, Heather; Shea, Judy A.; Asch, David A.; Pellathy, Thomas; Driggers, Jay; et al.
Purpose: To test whether employer matching of employees' monetary contributions increases employees' (1) participation in deposit contracts to promote weight loss and (2) weight loss. Design: A 36-week randomized trial. Setting: Large employer in the northeast United States. Participants: One hundred thirty-two obese employees. Interventions: Over 24 weeks, participants were asked to lose 24 pounds and randomized to monthly weigh-ins or daily weigh-ins with monthly opportunities to deposit 1 to 3 per day that was not matched, matched 1:1, or matched 2:1. Deposits and matched funds were returned to participants for each day they were below their goal weight. Measures: Rates of making ≥1 deposit, weight loss at 24 weeks (primary outcome), and 36 weeks. Analysis: Deposit rates were compared using χ 2 tests. Weight loss was compared using t tests. Results: Among participants eligible to make deposits, 29% made ≥1 deposit and matching did not increase participation. At 24 weeks, control participants gained an average of 1.0 pound, whereas 1:1 match participants lost an average of 5.3 pounds ( P = .005). After 36 weeks, control participants gained an average of 2.1 pounds, whereas no match participants lost an average of 5.1 pounds ( P = .008). Conclusion: Participation in deposit contracts to promote weight loss was low, and matching deposits did not increase participation. For deposit contracts to impact population health, ongoing participation will need to be higher.